Full Employment at Whatever Cost: Comment - Smithies, Arthur (Quarterly Journal of Economics, 1950)
Journal Article Full Employment at Whatever Cost: Comment Get access Arthur Smithies Arthur Smithies Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 4, November 1950, Pages 642–647, https://doi.org/10.2307/1884394 Published: 01 November 1950